Exploring healthcare professionals¿ views of the acceptability of delivering interventions to promote healthy infant feeding practices within primary care: a qualitative interview study - Hayes, Catherine (My University, 2021)
Objective: Early-life nutrition plays a key role in establishing healthy lifestyles and preventing chronic disease. This study aimed to (1) explore healthcare professionals' (HCP) opinions on the acceptability of and factors influencing the delivery of interventions to promote healthy infant feeding behaviours within primary care and (2) identify proposed barriers/enablers to delivering such interventions during vaccination visits, to inform the development of a childhood obesity prevention intervention. Design: A qualitative study design was employed using semi-structured telephone interviews. Data were analysed using qualitative content analysis; findings were also mapped to the Theoretical Framework of Acceptability (TFA). Setting: Primary care in Ireland. Participants: Twenty-one primary care-based HCP: five practice nurses, seven general practitioners, three public health nurses, three community dietitians and three community medical officers. Results: The acceptability of delivering interventions to promote healthy infant feeding within primary care is influenced by the availability of resources, HCP's roles and priorities, and factors relating to communication and relationships between HCP and parents. Proposed barriers and enablers to delivering interventions within vaccination visits include time constraints v. opportunistic access, existing relationships and trust between parents and practice nurses, and potential communication issues. Barriers/enablers mapped to TFA constructs of Affective Attitude, Perceived Effectiveness and Self-Efficacy. Conclusions: This study provides a valuable insight into HCP perspectives of delivering prevention-focused infant feeding interventions within primary care settings. While promising, factors such as coordination and clarity of HCP roles and resource allocation need to be addressed to ensure acceptability of interventions to HCP involved in delivery.
PUBLISHED
Keywords: Childhood obesity; Early-life nutrition; Infant feeding; Intervention; Prevention; Primary care